2022
DOI: 10.48550/arxiv.2202.05867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photodissociation and X-Ray Dominated Regions

Abstract: The radiation from stars and active galactic nuclei (AGN) creates photodissociation regions (PDRs) and X-ray dominated regions (XDRs), where the chemistry or heating are dominated by far-ultraviolet (FUV) radiation or X-ray radiation, respectively. PDRs include a wide range of environments from the diffuse interstellar medium to dense star-forming regions. XDRs are found in the center of galaxies hosting AGN, in protostellar disks, and in the vicinity of X-ray binaries. In this review, we describe the dominant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 409 publications
(719 reference statements)
0
24
0
Order By: Relevance
“…This value is at the lower end of the distribution found for QSOs at this redshift (Walter et al 2022;Decarli et al 2018;Shao et al 2019). The neutral gas mass in the disk, based on [CII] emission, can be derived with the relation from Hailey-Dunsheath et al (2010) (see also Bischetti et al 2019b), where X C + is the [CII] fraction per hydrogen atom, T is the gas temperature, n is the gas density, and n crit ∼ 3 × 10 3 cm −3 is the [CII]λ158µm critical density for collisions with neutral hydrogen that frequently occur in photo-dissociation regions (PDRs; Wolfire et al 2022;Hollenbach & Tielens 1999). We estimated the lower limit for the molecular mass in the regime n n crit (Maiolino et al 2005;Aalto et al 2012Aalto et al , 2015, and we considered a X C + ∼ 10 −4 and a gas temperature of 200 K, both typical of PDRs (Maiolino et al 2005;Hailey-Dunsheath et al 2010;Cicone et al 2015;Bischetti et al 2019a).…”
Section: [Cii] Distribution and Kinematicsmentioning
confidence: 99%
“…This value is at the lower end of the distribution found for QSOs at this redshift (Walter et al 2022;Decarli et al 2018;Shao et al 2019). The neutral gas mass in the disk, based on [CII] emission, can be derived with the relation from Hailey-Dunsheath et al (2010) (see also Bischetti et al 2019b), where X C + is the [CII] fraction per hydrogen atom, T is the gas temperature, n is the gas density, and n crit ∼ 3 × 10 3 cm −3 is the [CII]λ158µm critical density for collisions with neutral hydrogen that frequently occur in photo-dissociation regions (PDRs; Wolfire et al 2022;Hollenbach & Tielens 1999). We estimated the lower limit for the molecular mass in the regime n n crit (Maiolino et al 2005;Aalto et al 2012Aalto et al , 2015, and we considered a X C + ∼ 10 −4 and a gas temperature of 200 K, both typical of PDRs (Maiolino et al 2005;Hailey-Dunsheath et al 2010;Cicone et al 2015;Bischetti et al 2019a).…”
Section: [Cii] Distribution and Kinematicsmentioning
confidence: 99%
“…Intensity mapping experiments aim to detect the large-scale collective line emission from galaxies using widefield spectral mapping. The [CII] line at 158 µm is one of the main cooling lines of the interstellar medium (e.g., Tielens & Hollenbach 1985;Wolfire et al 2022). Observational studies at low redshift (e.g., De Looze et al 2014;Herrera-Camus et al 2015) and high redshift (e.g., Capak et al 2015;Schaerer et al 2020;Carniani et al 2020) found a non-evolving and nearlylinear empirical correlation between [CII] luminosity and SFR.…”
Section: Introductionmentioning
confidence: 99%
“…In their most general definitionneutral gas regulated by FUV radiation -, PDRs represent the dominant fraction of the neutral atomic and molecular gas in the ISM of starforming galaxies [1,3]. Indeed, except for the cold and dense molecular cores associated with the first stages of star formation, most of the ISM (in volume and mass) is effectively at A V < 8 mag.…”
Section: Pdrs Everywherementioning
confidence: 99%